Energetic and Economic Feasibility of RDF to Energy Plant for a Local Thai Municipality - Narawute Srisaeng (2018)
© 2017 The Authors. Management of waste is a main concern and one of the most crucial issues in modern society. Effective waste management considers prevention, recycling, and handling of waste in such a way that most effectively protects human health and the environment. Energy recovery is one of the accepted options in managing solid waste. In the present paper, a waste-to-energy conversion plant utilizing refuse derived fuel (RDF) with appropriate combustion technology was proposed for a local municipality in Lampang, Thailand. Realistic waste quantity and composition were estimated. Mass and energy analyses as well as an economic feasibility survey were carried out to evaluate performance and benefits of the proposal. With up to 220 tons of RDF available daily, it was suggested that a power plant project between 5 to 13 MW e generation capacity may be developed. For a baseline case of 5 MW e , the project is economically feasible with tolerance to ± 50% fluctuation in total capital cost, electricity sale price and tipping fee.